2007
DOI: 10.1094/cchem-84-4-0337
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Quantification, and Characterization of Phenolics Extracted with the Aid of Sonication from Rice Bran

Abstract: Phenolics are phytochemicals extensively distributed among plants that have been receiving great deal of attention for their functionality. Rice bran is a good source of phenolics, especially hydroxycinnamates. Although chemicals are commonly employed to isolate phenolics, the use of physical treatments such as sonication is still limited. This study was conducted to optimize a procedure to isolate phenolics from rice bran using sonication as a preextraction treatment. Sonication was optimized by varying outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…The ACE‐inhibitory activities of the extracts varied significantly with the maximum value of ACE‐inhibitory activity obtained in methanol extracts at 40 °C for 6 h (88.78%). Lower ACE activities were seen at higher temperatures of 50–60 °C after the 6‐h extraction or after the 8 h at all tested temperatures, which is explainable by observations showing that the use of markedly higher temperatures for more prolonged periods can destroy the chemical structure of biologically active compounds leading to decreased bioactivities (Onofre & Hettiarachchy, ).…”
Section: Resultsmentioning
confidence: 99%
“…The ACE‐inhibitory activities of the extracts varied significantly with the maximum value of ACE‐inhibitory activity obtained in methanol extracts at 40 °C for 6 h (88.78%). Lower ACE activities were seen at higher temperatures of 50–60 °C after the 6‐h extraction or after the 8 h at all tested temperatures, which is explainable by observations showing that the use of markedly higher temperatures for more prolonged periods can destroy the chemical structure of biologically active compounds leading to decreased bioactivities (Onofre & Hettiarachchy, ).…”
Section: Resultsmentioning
confidence: 99%
“…generally showed no significant variations with temperature and time of extraction; however, the highest total phenolic content was observed with extraction at 60ºC for 1 h. Likewise, the optimum temperature for extraction of phenolic compounds has previously been noted to be 60ºC in olive cake [23] and rice. [30] Hodzic et al [31] has reported that raising the temperature of extraction increases the extractability of phenolic compounds from rice, rye, oats, buckwheat, barley, wheat, and corn. Onofre and Hettiarachchy [30] showed that the phenolic yield from rice bran increased with a longer time of extraction at 95°C.…”
Section: Optimization Of Extracted Phenolic Compounds From Gingermentioning
confidence: 99%
“…[30] Hodzic et al [31] has reported that raising the temperature of extraction increases the extractability of phenolic compounds from rice, rye, oats, buckwheat, barley, wheat, and corn. Onofre and Hettiarachchy [30] showed that the phenolic yield from rice bran increased with a longer time of extraction at 95°C. As the time of extraction increased from 0.5 to 1 h, the content of extracted phenolic compounds was shown to increase in rice bran.…”
Section: Optimization Of Extracted Phenolic Compounds From Gingermentioning
confidence: 99%
See 1 more Smart Citation
“…Both the free and bound extracts were analysed for total phenol content, antioxidant capacity and phenolic acids as the majority of phenolic compounds, many of which also possess antioxidant activity, are bound covalently to the cell wall as the structural components of cellulose, lignin and proteins (Adom & Liu, ; Pérez‐Jiménez & Saura‐Calixto, ). Onofre & Hettiarachchy () stated that more than 70% of the phenolics in rice bran are cross‐linked to carbohydrates in the cell wall matrix. Owing to be the dominant phenolic acid in cereals, total phenol content was evaluated as ferulic acid equivalents.…”
Section: Resultsmentioning
confidence: 99%